Research advances on role of mitochondrial SIRT3 during renal ischemia-reperfusion injury - Ke Xin-yu; YANG Ding-ping (Linchuang shenzangbing zazhi)
Renal ischemia-reperfusion injury（RIRI）has such a high level of morbidity and mortality so that it lacks any effective treatment. Mitochondrial injury is one of the most important pathophysiological manifestations of acute kidney injury（AKI）. Essential for mitochondrial function and structural integrity, mitochondrial deacetylase silence information regulator 3（SIRT3）lessons RIRI through antagonizing oxidative stress, restoring mitochondrial membrane permeability, regulating mitochondrial dynamics and promoting mitochondrial biogenesis. It is a potential therapeutic target for RIRI. This review summarized the relevant researches of RIRI and SIRT3 in recent years.